Performance of Laying Hen Eggs on the Addition of Sprouts at Wakhid Farm, Magetan Regency - Catur Suci Purwati; Engkus Ainul Yakin; Febrian Nisa Ramadhani (Bantara Journal of Animal Science, 2021)
This study aimed to determine the performance of laying hen eggs on the addition of sprouts at Wakhid Farm, Magetan Regency. This research was conducted at Wakhid Farm, Magetan Regency. Sprouts were soaked for 1 day before being given to the treatment feed. This study used 4 types of treatment and each treatment consisted of 4 replications. P0 is control (50% corn + 15% bran + 35 concentrate), P1 is 50% corn + 15% bran + 35% concentrate + 5% sprouts, P2 is 50% corn + 15% bran + 35% concentrate + 10% sprouts and P3 which is 50% corn + 15% bran + 35% concentrate + 15% sprouts. Observation parameters include feed consumption, hen day production, egg weight and egg mass. Parameters observed in the study included feed consumption, egg production, hen day production, egg weight and egg mass. The research method used RAL (Completely Randomized Design) unidirectional pattern. The data obtained were then analyzed using ANOVA (Analysis of variance). If there is a significant treatment effect, then proceed with the DMRT Test (Duncan Multiple Range Test) to determine the differences between treatments. The data obtained showed that the performance of different eggs for each treatment sample had a significant effect on feed consumption, hen day production, egg weight and egg mass. The results showed that feed consumption was between 118.7 – 118.5 grams/day/head, hen day production was between 79.46 – 90.17%, egg weight was between 57.08 – 60.47 grams and egg mass was 43.94 – 56.55 grams. The conclusion was that the addition of sprouts did not affect feed consumption, hen day production and egg mass and had a significant effect on egg weight..